DIGITAL SAFETY FOR PRESCHOOL CHILDREN: A SCOPING REVIEW OF DIGITAL SAFETY FRAMEWORKS - ‘Aisyah ‘Inani Mohd. Saad; Mohd Nazri Abdul Rahman; Siti Nor Khalis Harun Narasid (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The use of technology among young children are increasing throughout time. The issues on digital safety that related to the children showed the high significant numbers. Therefore, in promoting the digital safety awareness to young children, the customized framework is needed due to young children is in the complex stage of development. This scoping review exploring the digital safety existing frameworks through literature search and mapping the digital safety relevant structure to preschool education children. The review highlights several frameworks in various elements and comparing the review with few countries. The insight from this review aim to develop the digital safety module especially for young children in Malaysia.